Violent behavior and physical activity of adolescents in residential care - Zurita-Ortega, F.; Castro-Sánchez, M.; Ubago-Jiménez, J. L.; Chacón-Cuberos, R.; Puertas-Molero, P.; González-Valero, G. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The present study aims to analyze the levels of violent behavior, self-esteem and practice of AF in adolescents who are in residential care ruling possible relationships between all variables with three hypotheses. The participation of a total of 203 adolescents allowed the registration and evaluation of violent conduct variables (Violent Behavior Scale in School), Self-esteem (as measured by the General Self-Esteem Scale Rosenberg) and Self Registration Sheet for values ​​AF issues. The results showed that adolescents living in the family home are regular team sports contact, that aggression levels are similar and that one third of them have low self- fulfilling two of the three hypotheses, and denoting mismatch between aggression, self-esteem and sport mode developed.